Food price inflation in East and Southeast Asia: Situation, driving forces, and the outlook - Zhou, Yunyi; Chen, Kevin Z. (AKI Agrarkozgazdasagi Intezet Nonprofit Kft, 2023)
Food price inflation has raised concerns about food insecurity and systemic crises in East and Southeast Asia, given the region’s population size, economic significance, and role in the international food market. COVID-19 repercussions, extreme climate- and weather-induced events, anthropogenic stressors such as global economic softness and the Russia-Ukraine war, and many other uncertainties enlarged the supply-demand imbalance of food. Those factors are not likely to ease in the short term and in the meantime, potentially new food crises are simmering in East and Southeast Asia. Meanwhile, China’s reopening and deepened intraregional integration have allowed the region’s food price situation to be less grim than elsewhere. This article conducts a political-economic analysis in order to identify the major forces driving recent food price inflation in the region as well as to explore what proactive measures can build greater food system resilience during the post-COVID-19 recovery. This article recommends that ountries refrain from imposing further export restrictions (whatever their form), and instead deepen dialogues and cooperation in order to facilitate food system resilience against the looming risks, such as El Niño.